Contribution of Intramyocellular Lipids to Decreased Computed Tomography Muscle Density With Age - Brennan, Nicholas A.; Fishbein, Kenneth W.; Reiter, David A.; Ferrucci, Luigi; Spencer, Richard G. (Frontiers in Physiology, 2021)
Skeletal muscle density, as determined by computed tomography (CT), has been shown to decline with age, resulting in increased frailty and morbidity. However, the mechanism underlying this decrease in muscle density remains elusive. We sought to investigate the role of intramyocellular lipid (IMCL) accumulation in the age-related decline in muscle density. Muscle density was measured using computerized tomography (CT), and IMCL content was quantified using in vivo proton magnetic resonance spectroscopy (1H-MRS). The study population consisted of 314 healthy participants (142 men, 32-98 years) of the Baltimore Longitudinal Study of Aging (BLSA). In addition to IMCL quantification, obesity-related covariates were measured, including body mass index (BMI), waist circumference, and circulating triglyceride concentration. Higher IMCL concentrations were significantly correlated with lower muscle density in older individuals, independent of age, sex, race, and the obesity-associated covariates (p<0.01). Lower muscle density was also significantly associated with greater age-adjusted IMCL, a variable we constructed using LOESS regression (p<0.05). Our results suggest that the accumulation of IMCL may be associated with a decrease in muscle density. This may serve to define a potential therapeutic target for treatment of age-associated decreased muscle function.